Використання добавок та льоду для зменшення впливу температури на бетон у жаркому кліматі - Лебедєв, Володимир Володимирович; Савченко, Д. О.; Вінник, Андрій Михайлович; Реука, Юрій Вікторович; М'ягкохліб, Ілля Іванович (Яроче́нко Я. В., 2022)
The purpose of the article is to investigate the features of the use of additives and ice to reduce the effect of temperature on the workability and curing of concrete in hot climates. To achieve the set goals, the tasks of conducting an analytical review on the issue of obtaining concrete with desired properties for monolithic concrete structures in a dry hot climate were solved in order to reduce the effect of temperature on the workability and care of concrete in the hot climate of Ukraine.
Keywords: технологія бетону; температура; бетонні роботи; цементи; екзотермія; жаркий клімат